The sum of the first three terms of a geometric progression is 126. If 14, 36, and 4 are added to each of these terms, respectively, then the new numbers form an arithmetic progression. Find the sixth term of the geometric progression


Respuesta :

Answer:

if r=4:

[tex]\displaystyle a_6=6144[/tex]

if r=1/4:

[tex]\displaystyle a_6=\frac{3}{32}[/tex]

Step-by-step explanation:

Geometric and Arithmetic Progressions

We define a geometric progression when each term [tex]a_n[/tex] is defined as the previous term [tex]a_{n-1}[/tex] times a constant called the common ratio. The iterative formula is

[tex]\displaystyle a_n=a_1.r^{n-1}[/tex]

In an arithmetic progression, each term is found by adding a constant called common difference, to the previous term

[tex]\displaystyle a_n=a_1+(n-1).r[/tex]

We are given the condition that the sum of the three first terms of a geometric progression is 126

[tex]\displaystyle a_1+a_2+a_3=126[/tex]

Using the iterative formula, we have

[tex]\displaystyle a_1+a_1.r+a_1.r^2=126[/tex]

Taking a common factor

[tex]\displaystyle a_1(1+r+r^2)=126....[eq\ 1][/tex]

We also know that if 14, 36, and 4 are added to each term, respectively, the new numbers form an arithmetic progression. It means they will have a common difference. The new numbers will be

[tex]\displaystyle a_1'=a_1+14[/tex]

[tex]\displaystyle a_2'=a_2+36[/tex]

[tex]\displaystyle a_3'=a_3+4[/tex]

The common difference between term 2 and term 1 is

[tex]\displaystyle a_2'-a_1'=a_2+36-a_1-14[/tex]

Using the iterative formula again

[tex]\displaystyle a_2'-a_1'=a_1.r-a_1+22[/tex]

The common difference between term 3 and term 2 is

[tex]\displaystyle a_3'-a_2'=a_3+4-a_2-36[/tex]

Using the iterative formula again

[tex]\displaystyle a_3'-a_1'=a.r^2-a.r-32[/tex]

Both common differences must be equal

[tex]\displaystyle a_1.r-a_1+22=a_1.r^2-a_1.r-32[/tex]

Rearranging

[tex]\displaystyle 2a_1r-a_1r^2-a_1=-54[/tex]

Solving for [tex]a_1[/tex]

[tex]\displaystyle a_1=\frac{54}{1-2r+r^2}......[eq\ 2][/tex]

Replacing in eq 1

[tex]\displaystyle \frac{54(1+r+r^2)}{1-2r+r^2}=127[/tex]

Dividing by 18 and cross-multiplying

[tex]\displaystyle 3+3r+3r^2=7-14r+7r^2[/tex]

Rearranging we have a second-degree equation

[tex]\displaystyle 4r^2-17r+4=0[/tex]

Factoring

[tex]\displaystyle (r-4)(4r-1)=0[/tex]

The solutions are

[tex]\displaystyle r=4\ ,\ r=\frac{1}{4}[/tex]

If r=4, and using eq 2

[tex]\displaystyle a_1=\frac{54}{1-8+16}=6[/tex]

Having [tex]a_1[/tex] and r, we compute [tex]a_6[/tex]

[tex]\displaystyle a_6=a_1.r^5=6.(4)^5[/tex]

[tex]\displaystyle a_6=6144[/tex]

If we use the other solution r=1/4

[tex]\displaystyle a_1=\frac{54}{1-\frac{1}{2}+\frac{1}{16}}=\frac{54}{\frac{9}{16}}[/tex]

[tex]\displaystyle a_1=96[/tex]

The sixth term is

[tex]\displaystyle a_6=96(\frac{1}{4})^5=\frac{96}{1024}[/tex]

[tex]\displaystyle a_6=\frac{3}{32}[/tex]

Both solutions are feasible

ACCESS MORE